Myocardial involvement characteristics by cardiac MR imaging in neurological and non-neurological Wilson disease patients - Wei Deng; Jie Zhang; Zhuoran Jia; Zixiang Pan; Zhen Wang; Huimin Xu; Liang Zhong; Yongqiang Yu; Ren Zhao; Xiaohu Li (Insights into Imaging, 2024)
Abstract Objectives To explore the characteristics of myocardial involvement in Wilson Disease (WD) patients by cardiac magnetic resonance (CMR). Methods We prospectively included WD patients and age- and sex-matched healthy population. We applied CMR to analyze cardiac function, strain, T1 maps, T2 maps, extracellular volume fraction (ECV) maps, and LGE images. Subgroup analyzes were performed for patients with WD with predominantly neurologic manifestations (WD‐neuro +) or only hepatic manifestations (WD‐neuro −). Results Forty-one WD patients (age 27.9 ± 8.0 years) and 40 healthy controls (age 25.4 ± 2.9 years) were included in this study. Compared to controls, the T1, T2, and ECV values were significantly increased in the WD group (T1 1085.1 ± 39.1 vs. 1046.5 ± 33.1 ms, T2 54.2 ± 3.3 ms vs. 51.5 ± 2.6 ms, ECV 31.8 ± 3.6% vs. 24.3 ± 3.7%) (all p < 0.001). LGE analysis revealed that LGE in WD patients was predominantly localized to the right ventricular insertion point and interventricular septum. Furthermore, the WD‐neuro + group showed more severe myocardial damage compared to WD‐neuro − group. The Unified Wilson Disease Rating Scale score was significantly correlated with ECV (Pearson’s r = 0.64, p < 0.001). Conclusions CMR could detect early myocardial involvement in WD patients without overt cardiac function dysfunction. Furthermore, characteristics of myocardial involvement were different between WD‐neuro + and WD‐neuro − , and myocardial involvement might be more severe in WD‐neuro + patients. Critical relevance statement Cardiac magnetic resonance enables early detection of myocardial involvement in Wilson disease patients, contributing to the understanding of distinct myocardial characteristics in different subgroups and potentially aiding in the assessment of disease severity. Key points • CMR detects WD myocardial involvement with increased T1, T2, ECV. • WD‐neuro + patients show more severe myocardial damage and correlation with ECV. • Differences of myocardial characteristics exist between WD‐neuro + and WD‐neuro − patients. Graphical Abstract